2020
DOI: 10.1001/jamaoto.2019.3967
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Discontinuation and Nonpublication of Head and Neck Cancer Randomized Clinical Trials

Abstract: IMPORTANCE Randomized clinical trials (RCTs) play an important role in clinical decision-making, and discontinuation or nonpublication of these trials are causes of great concern. The extent of discontinued or unpublished RCTs about head and neck cancer remains unclear. OBJECTIVE To assess the rate of discontinuation or nonpublication of RCTs involving patients with head and neck cancer. This objective was measured by observing 3 domains: discontinuation of trial, nonpublication of trial data, and feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 29 publications
1
45
1
Order By: Relevance
“…In the past decade, industry-funded trials (those supported by pharmaceutical and biotechnology companies) have become more prevalent [19]. A recent analysis of oncology RCTs from the 1990s to 2015 suggested industry trials are more likely to accrue [20], whereas in contrast, a specialty-specific study identified industry-funded trials were nearly four times less likely to publish their results [21]. Although there is concern regarding sponsorship bias, this was not identified in GI malignancy literature from the past decade, and the most significant threat found in this arena is nonpublication bias.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, industry-funded trials (those supported by pharmaceutical and biotechnology companies) have become more prevalent [19]. A recent analysis of oncology RCTs from the 1990s to 2015 suggested industry trials are more likely to accrue [20], whereas in contrast, a specialty-specific study identified industry-funded trials were nearly four times less likely to publish their results [21]. Although there is concern regarding sponsorship bias, this was not identified in GI malignancy literature from the past decade, and the most significant threat found in this arena is nonpublication bias.…”
Section: Discussionmentioning
confidence: 99%
“…Some potential causes include recruitment failure, trial adverse events and institutional staff changes. In a study by Briel M et al., there were 28 reasons for recruitment failure with the most common being overestimation of prevalence of eligible participants and prejudiced views of recruiters and participants ( Briel et al., 2016 ; Johnson et al., 2019 ). Therefore, clinical trials should plan protocols carefully to avoid waste of medical resources.…”
Section: Discussionmentioning
confidence: 99%
“…Unpublished research hinders medical advancement. Discoveries should be reported regardless of the results [1], and publication bias may lead to false and inappropriate conclusions [2]. Unpublished or incomplete clinical trials also waste research dollars that could have otherwise been allocated to other more fruitful efforts.…”
Section: Introductionmentioning
confidence: 99%